2(6z-1)-5(z+8)=3(z+1)

Simple and best practice solution for 2(6z-1)-5(z+8)=3(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6z-1)-5(z+8)=3(z+1) equation:


Simplifying
2(6z + -1) + -5(z + 8) = 3(z + 1)

Reorder the terms:
2(-1 + 6z) + -5(z + 8) = 3(z + 1)
(-1 * 2 + 6z * 2) + -5(z + 8) = 3(z + 1)
(-2 + 12z) + -5(z + 8) = 3(z + 1)

Reorder the terms:
-2 + 12z + -5(8 + z) = 3(z + 1)
-2 + 12z + (8 * -5 + z * -5) = 3(z + 1)
-2 + 12z + (-40 + -5z) = 3(z + 1)

Reorder the terms:
-2 + -40 + 12z + -5z = 3(z + 1)

Combine like terms: -2 + -40 = -42
-42 + 12z + -5z = 3(z + 1)

Combine like terms: 12z + -5z = 7z
-42 + 7z = 3(z + 1)

Reorder the terms:
-42 + 7z = 3(1 + z)
-42 + 7z = (1 * 3 + z * 3)
-42 + 7z = (3 + 3z)

Solving
-42 + 7z = 3 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-42 + 7z + -3z = 3 + 3z + -3z

Combine like terms: 7z + -3z = 4z
-42 + 4z = 3 + 3z + -3z

Combine like terms: 3z + -3z = 0
-42 + 4z = 3 + 0
-42 + 4z = 3

Add '42' to each side of the equation.
-42 + 42 + 4z = 3 + 42

Combine like terms: -42 + 42 = 0
0 + 4z = 3 + 42
4z = 3 + 42

Combine like terms: 3 + 42 = 45
4z = 45

Divide each side by '4'.
z = 11.25

Simplifying
z = 11.25

See similar equations:

| 3x-3=x+3 | | 48=12h | | 3x=3x-3 | | (6x^2)+10x= | | 23n=115 | | -16x^2+96x-576=0 | | c^3d^2(c^2d-2d)=0 | | 2x^5-12x^3=-16x | | 4a^2+10a=12 | | x^2+6x-91= | | 2-4y=30+3y | | d-125=75 | | (6s^2)(2s^2)-(3s^4)(4s^3)=0 | | 50-y=30 | | w+349=761 | | 64s^2+144s+81= | | 86+m=107 | | 2=m-3+c | | 71=b-29 | | 18=-2+w | | 60=n+30 | | 2(x-2)=7x-19 | | 12s^4-12s^7=0 | | s=180-360 | | p-11=12 | | 8[3m-2]-7m=0 | | 7=-9+22 | | 19+t=51 | | n(3+n)=n^2+4n | | x-8=-9 | | -11b+4=15 | | 5=x-20 |

Equations solver categories